Vinland saga. Book four - Yukimura, Makoto, 1976- (Kodansha, 2014)
"Pushed to the brink of despair after his father attempted to have him killed, Prince Canute has experienced an awakening, transforming him from a timid, gentle boy into a clear-eyed man with the heart of a king. But a king needs a crown, and Canute now knows that nothing will be given to him. If he wants to rule, he will have to prove his ruthlessness with a plot that will change the fate of the kingdom and spatter the throne with blood! Meanwhile, Thorfinn watches events unfold that could steal away the vengeance he has waited so long to achieve" --